y=(y-50)

Simple and best practice solution for y=(y-50) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=(y-50) equation:


Simplifying
y = (y + -50)

Reorder the terms:
y = (-50 + y)

Remove parenthesis around (-50 + y)
y = -50 + y

Add '-1y' to each side of the equation.
y + -1y = -50 + y + -1y

Combine like terms: y + -1y = 0
0 = -50 + y + -1y

Combine like terms: y + -1y = 0
0 = -50 + 0
0 = -50

Solving
0 = -50

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5x+45=-4x | | 106(12x+34)=180 | | 48=81 | | 1/2(t+7)=11 | | 6x^2-4x= | | -x/x+2=-1+1/x-3 | | -4y+3x=24 | | 5x-15=-3x+49 | | -5x-2y=-13 | | -19=x/-4 | | 2/3m=-1/9 | | 4x+10=80+3x | | 2x+5*2=4 | | 4-2x=5-3x | | 2*2+5y=4 | | 81-u=174 | | 6.6/(15-d)=0.6 | | f(5x)=x^2-12 | | 8*1-3y=5 | | 7(5)+4(-6)=2 | | -1=6(3)-4 | | 2-3/4y=8 | | 2x+5*.1=4 | | 4x-8=-2x+34 | | 2x-3(5x-8)= | | 7x+36=-2x | | 4*1.5= | | 9x-7x=8 | | 5x-10=-3x+22 | | 6x-12=-2x+36 | | 4x-16=-4x+16 | | 500/2.3=x/600 |

Equations solver categories